Lipid Profile of Cholelithiasis Patients at Dr. Mohammad Hoesin Central General Hospital, Palembang - Florettira, Mutiara Tri; Manawan, Efman Efraim Ulrich; Subandrate, Subandrate (JBN (Jurnal Bedah Nasional); Vol 6 No 2 (2022): JBN (Jurnal Bedah Nasional), 2022)
Aim : To determine the lipid profile of cholelithiasis patients at Dr. Mohammad Hoesin Central General Hospital, Palembang. Methods: This study was an observational descriptive study. The data were obtained from medical records in the Medical Record Centre of Dr. Mohammad Hoesin Hospital during the period of 1 January 2016 – 30 June 2019 by total sampling technique. Collecting data from medical record were patient’s age, gender, body mass index (BMI), occupation and lipid profile. Results: Most cholelithiasis patients were > 40 years old (69.6% of 253 patients), female (62.1% of 253 patients), normal BMI (42.6% of 195 patients), and a housewife (38% of 163 patients). The mean of total cholesterol level in 38 patients was 191.82 ± 49.63 mg/dL (104 – 350 mg/dL), the mean triglyceride level in 32 patients was117.16 ± 43.46 mg/dL (36 – 212 mg/dL), the mean of LDL level in 35 patients was 125.31 ± 36.64 mg/dL (62 – 244 mg/dL) and the mean HDL level in 36 patients was 43.33 ± 14.35 mg/dL (17 – 84 mg/dL). Conclusion: Almost all cholelithiasis patients at Dr. Mohammad Hoesin Central General Hospital, Palembang had normal lipid profile.